Perancangan Prototype Deteksi Kebocoran Gas dengan Sensor MQ2 dan NodeMCU ESP8266 - Anggie Maesyaroh; Hendra Marcos (P3M Politeknik Negeri Cilacap, 2025)
This research successfully developed a prototype of an IoT-based LPG gas leak detection system using an MQ-2 sensor and NodeMCU ESP8266 with digital output. The system works in binary to detect the presence or absence of gas and send notifications via Telegram. The research method includes hardware design, microcontroller programming using Arduino IDE, and system testing through 10 simulated gas leaks at a distance of 5 cm. The test results show that the prototype functions very well, achieving perfect detection accuracy (100%) in all trials. The system can respond to gas leaks quickly, having an average response time of 1.6 seconds and sending Telegram notifications in less than 3 seconds. Importantly, the system did not give false alarms under normal conditions. The prototype features three layers of alerts: a buzzer sound, a red LED indicator, and a Telegram notification that can be accessed from anywhere. With a relatively affordable production cost, the system offers an effective, reliable, and affordable gas leak early detection solution for household safety.